On the generic names proposed in Chrysomelidae (Coleoptera) by Gustaf Johan Billberg - Bezděk, Jan; Biondi, Maurizio (Zootaxa, 2018)
The genus names proposed by Billberg (1820a) for Chrysomelidae are reviewed. Mesops Billberg, 1820 is considered an unavailable name. Apelma Billberg, 1820 is confirmed as synonym of Macroplea Samouelle, 1819. Chrysomela concolor Fabricius, 1781, the type species of Isosoma Billberg, 1820, is a representative of Phygasia Dejean, 1836. To save the generic name Phygasia we propose Isosoma as nomen oblitum for Phygasia (nomen protectum). Chrysomela flavipes Linnaeus, 1767 is designated as type species of Lyperus Billberg, 1820 and Lyperus is proposed as new synonym of Luperus Geoffroy, 1762. Galleruca lausoniae Fabricius, 1798 is designated as type species of Adimus Billberg, 1820 and Adimus is proposed as new synonym of Altica Geoffroy, 1762. Galleruca lausoniae Fabricius, 1798 is confirmed as synonym of Altica caerulea (Olivier, 1791).